Praktik Pembulatan Harga Dalam Jual Beli BBM di SPBU Perspektif UU Nomor 8 Tahun 1999 - Fitriana, Alvi Lailatuz Zahro; Pakih, Ilham; Maromi, Nailul; Kamila, Sopwa (Media Hukum Indonesia (MHI), 2024)
Price rounding is the practice of adjusting the price of goods by rounding it either up or down. In fuel purchase transactions, this often occurs when consumers fill their tanks (full-tank purchases), and the price charged by gas station attendants does not match the amount displayed on the fuel dispenser screen. If such practices continue unchecked, they could become a habit that disadvantages consumers.This study aims to analyze the phenomenon of price rounding in fuel purchases at gas stations from the perspective of consumer protection laws. This article employs a juridical-empirical research method, using a statute approach grounded in legal provisions and regulations, alongside a conceptual approach. The research includes a detailed review of existing laws, interviews with consumers, and library research. Data analysis is carried out using descriptive-analytical techniques.According to Law No. 8 of 1999 on Consumer Protection, the practice of price rounding in fuel transactions at gas stations constitutes a violation of consumer rights, particularly the right to receive accurate and reliable information. Furthermore, it infringes on the consumer's right to obtain goods that correspond to the payment made. If left unaddressed, such practices could harm consumers by failing to uphold their rights.